(untitled) (Argos, 2025)
The gathering of women in the Assembly is the key piece in the consummation of the utopian change planned by Praxagora, the heroine of Assemblywomen, a project which consists in leaving políticaI affairs in women’s charge to carry out a communist revolution. Aristophanes, however, chooses to relegate the event to the backstage. Instead, he grants his audience two different images of the same episode: the rehearsal of women previous to the Assembly and the comments of Chremes, who attended the public meeting. Both scenes, analyzed inside the frame of theater communication, expose the connection between the histrionic ability and the rhetoric, between acting and politics.